Situational factors on the impulse buying behavior of undergraduates on Shopee: The moderating effect of ease of use - Fernandez, Arianne Romelle R. (Animo Repository, 2022)
Online shopping has been an increasingly popular method for purchasing items among the young consumers located in the Philippines. Moreover, online shopping sites and mobile applications have been emerging to accommodate the demand for the market set by the growth of digital developments. Accordingly, the study aimed to understand the situational factors that influence impulse buying behavior that may be applied to online shopping, considering how they have been acknowledged as top drivers of purchases. The researchers wished to aid marketers and business owners in identifying whether these actions remain effective in helping their businesses progress despite prevalence in the online scene. The particular e-commerce undertaken was Shopee. The situational factors analyzed were price discounts, free shipping, influencer marketing, and availability of money. Ease of use being the moderator to which impulse buying behavior is being subjected was applied to the research as well. The rationale for such lies on the interaction of individuals with the said platform throughout the impulse buying journey. This study applied a quantitative research design that assessed the impulse buying behavior of the undergraduate students in the Philippines. A convenience sampling method was applied towards its target sample size of 385, through the use of the research instrument via Google Forms. Moderated linear regression and multiple linear regression were applied for the analysis of the relationships among dependent, independent, and moderating variables. The study found that undergraduates have an average level of impulse buying behavior, driven primarily by free shipping and price discounts. When moderated by ease of use, free shipping and availability operated best as determinants. Notwithstanding, the researchers suggest exploring other situational as well as internal factors given low, but positive explanatory powers of the investigated variables. Specifically, a modern but similar variable that can be considered a more effective factor is social media. Likewise, Shopee and its features can be explored further upgraded, in such a way that would give emphasis to the situational factors. Lastly, consumers may be better driven to impulse buy if price discounts and free shipping are validated.